Reduction of azo dyes by intestinal anaerobes. - Chung, K T (1978)
Reduction of seven azo dyes (amaranth, Ponceau SX, Allura Red, Sunset Yellow, tartrazine, Orange II, and methyl orange) was carried out by cell suspensions of predominant intestinal anaerobes. It was optimal at pH 7.4 in 0.4 M phosphate buffer and inhibited by glucose. Flavin mononucleotide caused a marked enhancement of azo reduction by Bacteroides thetaiotaomicron. Other electron carriers, e.g., methyl viologen, benzyl viologen, phenosafranin, neutral red, crystal violet, flavin adenine dinucleotide, menadione, and Janus Green B can replace flavin mononucleotide. These data suggest that an extracellular shuttle is required for azo reduction.